Strategic use of English quantifiers in the reporting of quantitative information - Macuch Silva, Vinicius; Lorson, Alexandra; Franke, Michael; Cummins, Chris; Winter, Bodo (Discourse processes, 2024)
This study investigates how quantifiers are used strategically to serve different argumentative goals. We report two experiments on how English speakers describe the results of school exams when being instructed to frame their descriptions either as a good or bad outcome. Experiment 1 shows that participants have clear preferences for specific quantifier combinations in this task. Experiment 2 shows that, in situations where producing descriptions that meet one's argumentative goals is difficult (i.e. framing very bad outcomes positively), participants tend to use quantifiers that are informationally weaker than other salient alternatives. Experiment 2 also shows that people have a bias to frame outcomes positively, even when the task asks them to frame them negatively. Put together, these results shed light on the question of how language users strategically explore different linguistic strategies to communicate quantity in pragmatically favorable ways, including how quantifiers are used vis-`a-vis other lexical expressions of quantity.